Antara Rasisme dan Xenofobia di Korea Selatan: Studi Hermeneutika pada Lagu Black Happiness Yoon Mi-rae - Utami, Gita (East Asian Review, 2025)
South Korea is one of the countries with an advanced education system and robust industrial development. This stands in stark contrast to the numerous deep-rooted social issues, which have led to global social criticism of South Korea. Social problems such as xenophobia, racism, and discrimination currently lack adequate legal frameworks to support minority groups. This study aims to explore the meaning of Yoon Mi-rae's song "Black Happiness" from a hermeneutic perspective. The methodology employed in this research is a complementary approach to hermeneutics as proposed by Paul Ricoeur and Hans-Georg Gadamer. The findings of this study reveal that the meaning of "Black Happiness" emphasizes healing wounds and self-acceptance. This research concludes that every individual has the right to live freely, to be accepted, and to be valued. Every person is entitled to an inclusive life and to live without being judged based on their background.